Making Hospitals More Dementia Friendly: An Inclusive, User-Centered Approach - Farsetta DL; Endicott SE; Woywod P; Bratzke LC (Journal of Healthcare Leadership)
Diane L Farsetta,1,* Sarah E Endicott,1,* Paula Woywod,1,2 Lisa C Bratzke1 1School of Nursing, University of Wisconsin–Madison, Madison, WI, USA; 2UW Hospital and Clinics, Madison, WI, USA*These authors contributed equally to this workCorrespondence: Diane L Farsetta, University of Wisconsin–Madison, 4149 Signe Skott Cooper Hall, University of Wisconsin–Madison, 701 Highland Ave, Madison, WI, 53705, USA, Email farsetta@wisc.eduPurpose: People living with dementia and their care partners identify interactions with the healthcare system as among their greatest challenges. Many hospital staff do not feel prepared to care for people living with dementia. This contributes to poor outcomes for patients living with dementia, frustration and confusion for care partners, and distress for hospital staff.Patients and Methods: An academic project team with expertise in education, geriatrics, simulation, and community engagement, who had previously developed dementia-friendly training materials for classroom and community use, designed a dementia-friendly hospital toolkit. Applying principles of user-centered design, the project team consulted with care partners of people living with dementia, hospital staff, hospital leadership, and advocates from communities disproportionately impacted by dementia to identify and address the needs of patients, care partners, hospital staff, and hospital leadership.Results: The project team developed a dementia-friendly hospital toolkit, which includes training materials for hospital staff across roles and an organizational guide to facilitate uptake by a wide range of hospitals. In multiple rounds of pilot testing, hospital staff rated toolkit training activities highly, reporting new insights and applying the knowledge or skills gained in their professional roles. Five hospitals, ranging from large academic centers to rural critical access hospitals, used the toolkit to assess needs, develop plans, and organize training sessions for staff. All hospitals reported receiving positive feedback from staff, meeting staff learning objectives, and intending to continue using the toolkit to meet their dementia-friendly goals.Conclusion: Following an inclusive, user-centered approach to developing dementia-friendly training materials allowed the project team to address the needs of key partners: people living with dementia, their care partners, hospital staff, and hospital leadership. Based on the positive responses from hospital pilot partners, the project team is supporting wider dissemination of the dementia-friendly hospital toolkit.Keywords: dementia care, professional development, hospital, user-centered design